Фауна трематод диких гусиных (Anseriformes) Северо-Западного Причерноморья - Искова, Н.И. (Вестник зоологии, 1972)
As a result of studying trematodofauna in 222 individuals of 18 Anseriformes species 53 species of trematodes are found. Anacetabulitrema samarae, Eucotyle zvehri, Paramo- nostomum elongatum are registered in the USSR fauna for the first time and Echinopa- cyphium nordiana, Hypoderaeum skrjabini, Levinseniella brachysoma, L. bucephalae, L. propinqua, Psilochasmus longicirratus, Renicola sp., Paramonostomum pseudoalveatum, P. alveatum, Trichobilharzia ocellata — in the Ukrainian fauna. 34 species of trematodes are found only in the birds of this order, 14 species being specific for Anseriformes, 20 may occur in representatives of other orders. Representatives of the families Echinostomatidae (15 species), Microphallidae (8 species) and liotocotylidae (6 species) proved to be the most distributed in Anseriformes.